2021
DOI: 10.5334/gh.1002
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mutation Annotation and Pedigree for Pulmonary Arterial Hypertension Patients in Han Chinese Patients

Abstract: Background:The etiology of pulmonary arterial hypertension (PAH) in the Han Chinese population is poorly understood. Objectives: The aim of this study was to assess gene variants and associated functional annotations for PAH in Han Chinese patients. Methods: This is an ethnicity-based multi-centre study. Blood samples were collected from 20 PAH patients who volunteered for the study, and genetic tests were performed. The DAVID database was used to functionally annotate the genes BMPR2, ALK1, KCNK3, CAV1, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Later, in different PAH cohorts from different countries, 22 additional missense variants were identified in KCNK3: G203D, A114T, A114V, L214R, L214P, K145M, R51L, R390H, F225L, G174S, Y85H, R359T, V206M, E182Q, G236A, V206L, L214P and S31W (Best et al, 2017;Cunningham et al, 2019a;Eichstaedt et al, 2022) (Table 1 and Fig. 3; Eyries et al, 2019;Gräf et al, 2018;Haarman et al, 2020;Higasa et al, 2017;Liang et al, 2014;Navas Tejedor et al, 2017;Wang et al, 2019Wang et al, , 2021Xi et al, 2016;Yang et al, 2018;Zhang et al, 2019;Zhu et al, 2018Zhu et al, , 2019. In addition, Wang et al identified a variant in the 5 UTR of KCNK3 in the PAH cohort (Liang et al, 2014;Wang et al, 2019) (Table 1).…”
Section: Kcnk3 In Pathological Conditionsmentioning
confidence: 99%
“…Later, in different PAH cohorts from different countries, 22 additional missense variants were identified in KCNK3: G203D, A114T, A114V, L214R, L214P, K145M, R51L, R390H, F225L, G174S, Y85H, R359T, V206M, E182Q, G236A, V206L, L214P and S31W (Best et al, 2017;Cunningham et al, 2019a;Eichstaedt et al, 2022) (Table 1 and Fig. 3; Eyries et al, 2019;Gräf et al, 2018;Haarman et al, 2020;Higasa et al, 2017;Liang et al, 2014;Navas Tejedor et al, 2017;Wang et al, 2019Wang et al, , 2021Xi et al, 2016;Yang et al, 2018;Zhang et al, 2019;Zhu et al, 2018Zhu et al, , 2019. In addition, Wang et al identified a variant in the 5 UTR of KCNK3 in the PAH cohort (Liang et al, 2014;Wang et al, 2019) (Table 1).…”
Section: Kcnk3 In Pathological Conditionsmentioning
confidence: 99%
“…The present study reported five female patients with BMPR2 variants. Although male patients have been reported to have a higher BMPR2 mutation rate compared to female patients [ 23 ], the female patients had higher penetrance than the males, with 42% and 14%, respectively [ 4 , 24 , 25 ]. Moreover, it has been shown that being female is the single most definitive modifier for the penetrance of BMPR2 mutations in PAH [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATP13A3 encodes a P-type ATPase, a cation channel transporter, and has been reported to be associated with PAH [ 6 , 19 , 47 ]. The monoallelic ATP13A3 variant has been associated with adult-onset PAH [ 2 , 4 , 5 , 20 ], and Machado et al demonstrated that biallelic ATP13A3 variants in childhood-onset PAH are characterized by extreme morbidity and mortality [ 48 ]. The PAH patients with or without ATP13A3 genetic variants are reported in Supplemental Table S4 , which illustrates that there were higher mPAP values (52 ± 7 vs. 38 ± 13 mmHg, p = 0.043) in the ATP13A3 variant subgroup compared to the non-ATP13A3 variant carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary arterial hypertension (PAH) is defined as mean pulmonary arterial pressure (mPAP) > 20 mmHg at rest as assessed by right heart catheterization, pulmonary arterial wedge pressure ≤ 15 mmHg, and pulmonary vascular resistance > 2 wood units, according to the classification of 2022 European Society of Cardiology (ESC)/European Respiratory Society (ERS) guidelines [ 1 ]. Pathologic progressions of vascular remodeling leads to pulmonary hypertension, right-sided heart failure, and death, once compensatory mechanisms have failed [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%